Mortality of haemodialysis patients with and without chronic itch: A follow-up study of the german epidemiological hemodialysis itch study (GEHIS) - Grochulska, Katarzyna; Ofenloch, Robert; Weisshaar, Elke (Acta dermato-venereologica, 2019)
The GEHIS (German Epidemiological Hemodialysis Itch Study) is a representative cohort study started in 2013 with 860 haemodialysis (HD) patients in 25 German dialysis units. Chronic itch (CI) has been reported to be a poor prognostic marker for patients on HD; however, this has not been investigated in a representative patient cohort. In 2017, all HD patients were contacted again to investigate mortality in those with and without CI and to identify its determinants. Patients' characteristics, study instruments and CI were assessed, as in 2013. The response rate was 84.2% (n = 724). One-year mortality was 15.3%. Mortality was significantly higher in those with secondary scratch lesions compared with those with non-affected skin. This was also true after controlling for age and sex in a multivariate model. This study demonstrates a high mortality in HD patients; however, mortality depends on itch intensity, not on the occurrence of CI itself.
Gesehen am 14.05.2019